A comparative study of characterisation of plasma electrolytic oxidation coatings on carbon steel prepared from aluminate and silicate electrolytes. (2nd January 2018) - Yang, Wenbin; Li, Qingbiao; Liu, Cancan; Liang, Jun; Peng, Zhenjun; Liu, Baixing
ABSTRACT: Two kinds of PEO coatings were prepared on low carbon steel from aluminate electrolyte and silicate electrolyte, respectively. The coating surface and cross-section morphologies were observed by scanning electron microscope. The elemental and phase compositions were investigated by energy-dispersive spectrometer and X-ray diffraction, correspondingly. The scratch test was employed to examine the adhesion of the PEO coating. The electrochemical tests were used to evaluate the anti-corrosion property of PEO coatings. It was found that more substrate was oxidised during PEO process under the same constant voltage for the same length of time in silicate electrolyte than that in aluminate electrolyte. Besides, the silicate PEO coating grew faster than aluminate PEO coating. Compared with the uniform distribution of elements in aluminate PEO coating, silicate PEO coating exhibited a two-layered structure. The two-layered structure of the silicate PEO coating led to a negative effect on the adhesion. The aluminate PEO coating showed a better anti-corrosion property because of its denser structure.